PENGARUH PEMBERIAN PUPUK NPK, ABMIX, DAN PUPUK KOMPOS CAIR MELALUI MEDIA TANAM AEROPONIK TERHADAP PERTUMBUHAN TANAMAN SELADA KERITING (Lactuca sativa L) - N Putri Sumaryani; Gek Wisky Ari (Emasains : Jurnal Edukasi Matematika dan Sains, 2016)
The use of aeroponics system is one alternative for horticultural growing vegetables such as curly lettuce. This study used three types namely NPK fertilizer, AB mix and liquid compost. This study aimed to determine the effect of NPK fertilizer, ABmix and liquid compost through aeroponic growing media on plant growth curly lettuce (Lactuca sativa L) and to know which is better fertilizer for plant growth curly lettuce (Lactuca sativa L). The formulation of the hypothesis proposed in this study is the alternative hypothesis (Ha) which says that there is influence of NPK fertilizer, ABmix and liquid compost through aeroponic growing media on plant growth curly lettuce (Lactuca sativa L). This type of research experiments conducted with the use of a pattern of "The Post Test Only Control Group Design" is implemented with three fertilizer NPK fertilizer, AB mix and liquid compost through aeroponic planting medium with five repetitions. The population in this study is a curly lettuce plants (Lactuca sativa L) of 500 plants and 300 samples of each treatment plant where there are 15 keriting.Data lettuce plants collected in this study is data on the number of curly lettuce plant fresh weight. The data obtained in this study was processed using analysis of variance (ANOVA) with the F test and significance level of 5% and 1%, if there are significant differences among treatment followed by LSD test. The results obtained by analysis of F for curly lettuce plant fresh weight was 225.98 while the limit for rejection of H0 at significance level of 5% and 1% by dk between groups = 3, dk in groups = 56 respectively are 2.77 and 4.15. The most optimal wet weight obtained at AB fertilizer mix.